1994
DOI: 10.1007/bf02445732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human defensins on the cytoplasmic Ca2+ content in platelets

Abstract: The effect of the total fraction of human defensins (HNP-1, HNP-2, and HNP-3) on the cytoplasmic Ca 2* content ([Ca2*]i) in the platelets of healthy donors was studied. At concentrations of 0.1-40 gg/ml and an incubation time of 10 mm defensins have no effect on [Ca~+]i in platelets labeled with Fura-2AM. However, at higher concentrations (100 ~tg/ml) they increased platelet [Ca2+]i . In addition, defensins (40 ~tg/ml) inhibited the Ca 2 § increase in platelets induced by thrombin, adenosine diphosphate, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…When washing off the PMN secretion we could not observe a significant change in phagocytosis, suggesting direct activation of macrophages by components of the PMN secretion rather than an opsonization of the bacteria to be responsible for the enhanced phagocytosis. This is supported further by measurements of intracellular Ca 2+ , which resemble a similar pattern, as activation in response to HBP [7,17], cathepsin G [18] and defensins [19] is similar to the macrophage activation by PMN secretion found in this study. Therefore, this group of PMN‐derived polypeptides and other PMN proteins are probable candidates in the effect described here.…”
Section: Discussionsupporting
confidence: 88%
“…When washing off the PMN secretion we could not observe a significant change in phagocytosis, suggesting direct activation of macrophages by components of the PMN secretion rather than an opsonization of the bacteria to be responsible for the enhanced phagocytosis. This is supported further by measurements of intracellular Ca 2+ , which resemble a similar pattern, as activation in response to HBP [7,17], cathepsin G [18] and defensins [19] is similar to the macrophage activation by PMN secretion found in this study. Therefore, this group of PMN‐derived polypeptides and other PMN proteins are probable candidates in the effect described here.…”
Section: Discussionsupporting
confidence: 88%
“…Our observation that HNPs induce platelet activation is in disagreement with conclusions made in previous studies. The group of Kubtiev reported that HNPs inhibit agonist‐induced platelet aggregation as well as agonist‐induced increase of platelet cytoplasmatic Ca 2+ levels [57,58]. However, in both studies an HNP‐enriched extract from human blood was used, whereas we used pure synthetic HNP‐1.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely described mechanism of action of antimicrobial peptides is the induction of membrane permeabilization through the formation of multimeric pores (28). Antimicrobial peptides can be cytotoxic at high concentrations (27), but specific peptides, at lower concentrations, have been shown to possess mitogenic, chemotactic or cytokine modulatory activities (29, 30), as well as acting to inhibit protein kinase C (31) and stimulate Ca ++ mobilization (32), signaling mechanisms of relevance to cold ischemic injury.…”
Section: Discussionmentioning
confidence: 99%